2013
DOI: 10.2188/jea.je20130006
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein and Prostate Cancer: An Overview

Abstract: Prostate cancer is a common disease in modern, developed societies and has a high incidence and mortality. High-density lipoprotein cholesterol (HDL-C) has recently received much attention as a possible risk marker of prostate cancer development and prognosis. In the present article, we summarized findings from epidemiologic studies of the association between HDL-C and prostate cancer. Low HDL-C level was found to be a risk and prognostic factor of prostate cancer in several epidemiologic studies, although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 34 publications
(102 reference statements)
1
38
2
Order By: Relevance
“…Although the primary mechanism by which HDL reduces cardiovascular disease risk is via reverse cholesterol transport [28], it is not known whether this same mechanism may impact PC growth. HDL has also been demonstrated to have anti-inflammatory, anti-proliferative and anti-oxidant properties [29] which may slow PC growth and progression, although epidemiologic evidence has been inconclusive [22]. Finally, high triglycerides have been associated with elevated levels of reactive oxygen species and oxidative stress, in addition to development of insulin resistance, all of which have been associated with prostate tumorigenesis [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the primary mechanism by which HDL reduces cardiovascular disease risk is via reverse cholesterol transport [28], it is not known whether this same mechanism may impact PC growth. HDL has also been demonstrated to have anti-inflammatory, anti-proliferative and anti-oxidant properties [29] which may slow PC growth and progression, although epidemiologic evidence has been inconclusive [22]. Finally, high triglycerides have been associated with elevated levels of reactive oxygen species and oxidative stress, in addition to development of insulin resistance, all of which have been associated with prostate tumorigenesis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies examined the association between cholesterol subfractions —low and high density lipoprotein (LDL and HDL, respectively) — and PC. While there is some evidence that elevated LDL [12, 20] and low HDL [10, 21] are associated with increased risk of aggressive PC, not all studies reported these findings [13, 15, 22], and the association between cholesterol subfractions and risk of PC recurrence has not been widely studied. Finally, evidence for an association between serum triglycerides and PC recurrence is mixed [14, 23].…”
Section: Introductionmentioning
confidence: 99%
“…HDL is one of the major carriers for cholesterol, which is an important regulator of cancer development (Cruz, Mo, McConathy, Sabnis, & Lacko, 2013). Epidemiologic studies suggest that low levels of HDL cholesterol and HDL particles are risk markers of cancer development and prognosis (Kotani et al, 2013; Vilchez, Martinez-Ruiz, Sancho-Rodriguez, Martinez-Hernandez, & Noguera-Velasco, 2014). As the primary receptor responsible for the selective internalization of cholesteryl ester from HDL molecules, the role of SR-BI in cancer development recently received increasing attention.…”
Section: Scavenger Receptors In Cancer Immunobiologymentioning
confidence: 99%
“…Additionally, it has been suggested that certain lipoprotein fractions, e.g. low-density lipoprotein (LDL) or high-density lipoprotein impact the activity of Akt, mitogen-activated protein kinase (MAPK), extracellular signal-regulated kinase (ERK)1/2 and Signal Transducer and Activator of Transcription 3 (STAT3) pathways and subsequently tumour proliferation, migration and invasion [23]. Zhang et al [24] recently showed in a case-control study of Chinese subjects that abnormal LDL elevation is prevalent in patients with RCC.…”
Section: Discussionmentioning
confidence: 99%